Extended exposure duration of cultured intestinal epithelial cell monolayers in characterizing hazardous and non-hazardous proteins. (May 2018) - Zimmermann, C.; Eaton, A.D.; Lanter, B.B.; Roper, J.; Hurley, B.P.; Delaney, B.
Abstract: Recent studies suggest that human derived intestinal epithelial cells (IECs) cultured as polarized monolayers on Transwell ® filters may respond differently when exposed to hazardous and non-hazardous proteins. This experimental platform was based on apical exposure of IEC monolayers to test proteins for 24 h followed by assessment of barrier integrity and cell viability. In this study, Caco-2 and T84 IEC polarized monolayers were evaluated for barrier integrity and cytotoxicity following exposure to hazardous and non-hazardous proteins for 24, 48 and 72 h. Hazardous proteins included Clostridium difficile toxin A (ToxA), Streptolysin O (SLO), Wheat Germ Agglutinin (WGA), and Phaseolus vulgaris haemagglutinin-E (PHA-E). Non-hazardous proteins included bovine serum albumin (BSA), porcine serum albumin (PSA), and fibronectin (Fbn). In general, evidence of diminished barrier integrity or cell viability observed following exposure to hazardous proteins for 24 h was more pronounced after 48 and 72 h for both IEC monolayers. Non-hazardous proteins exhibiting no impact following 24 h of exposure elicited minimal effects over longer exposure durations. These results support the utility of using cultured human IEC polarized monolayers to differentiate between hazardous and non-hazardous proteins and suggest that longer durations of exposure may further improve the ability to distinguish between them. Highlights: Non-hazardous proteins exhibited minimal adverse effects on cultured human IEC monolayers at various durations of exposure. Hazardous proteins produced adverse effects in human IEC monolayers at 48 and 72 h more frequently than at 24 h. Cultured human IEC monolayers may be useful in differentiating between non-hazardous and hazardous proteins.